Prediction of dynamic liquid level in water-producing shale gas wells based on liquid film model - Nie, Jie; Qiao, Lingxi; Wang, BenQiang; Wang, Weiyang; Li, Mingzhong; Zhou, Chenru (Frontiers in Earth Science, 2023)
The accumulation of liquid in shale gas wells will lead to an increase in bottom-hole pressure, and a decrease in production, even the shutdown of gas wells. Accurately predicting the variation of liquid height in shale gas wellbore and the corresponding production is helpful to determine the liquid accumulation status and the development of reasonable drainage construction plans. It can provide theoretical support for the efficient and stable production of shale gas wells. A predictive analysis model of shale gas wellbore liquid accumulation was established based on a liquid film carrying model, which considers the coupling of flow in the reservoir and wellbore in shale gas production system. This model can accurately predict the liquid accumulation height, production rate, and the bottomhole pressure changes in liquid-accumulating gas wells.A comparative analysis was conducted on the effect of wellbore structure on liquid accumulation characteristics in the typical upward-type and downward-type horizontal wells in the W block. In upwardtype horizontal wells, the liquid height increases slowly before the liquid accumulation fills the horizontal section, and the liquid height increases rapidly after the liquid accumulation fills the horizontal section.Compared to upward-type horizontal wells, the liquid height rises more quickly and the gas production rate is more sensitive to liquid accumulation in downward-type horizontal wells.